Seroprevalence of chlamydia trachomatis infection in Kashmiri women of reproductive age with mucopurulent cervicitis, infertility and ectopic pregnancy - a hospital based study - Hassan, Qurat U.; Mufti, Asma H.; Mufti, Samiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Chlamydia trachomatis is one of the most prevalent sexually transmitted infection worldwide. Objective was to find the seroprevalence of the Chlamydia trachomatis infection in women who suffer from infertility, mucopurulent cervicitis and ectopic pregnancy and to investigate the possible role of the chlamydial serology as a screening test by detection of the anti-Chlamydia IgG antibodies using enzyme-linked immunosorbent assay (ELISA). Methods: 160 women who attended the gynecology outpatient department (OPD) at a tertiary care hospital were screened for presence of chlamydia trachomatis IgG antibodies. Patients were categorized based on clinical diagnosis in: group I comprising of 120 patients [40 patients in each sub group - mucopurulent cervicitis (MPC); infertility; and ectopic pregnancy]; and group II comprising fertile women with no clinical signs and symptoms of mucopurulent cervicitis and no history of ectopic pregnancy and infertility. Patients were screened for IgG antibodies to Chlamydia trachomatis. Results: In our study 32.5% women with mucopurulent cervicitis were positive for Chlamydia trachomatis immunoglobulin G (CT IgG). In the infertile group, 22.5% of women were positive for chlamydia IgG antibodies. 30% of ectopic pregnancies were positive for chlamydia trachomatis IgG. Out of 40 patients who were taken as controls, 7.5% screened positive for Chlamydia IgG antibodies. Seroprevalence of Chlamydia trachomatis was 23.12% in our study. Conclusions: Our study has shown that significant proportion of our population harbor Chlamydia trachomatis. So, it becomes imperative that health and screening programs be employed to prevent spread of this infection and its long term sequelae in women of childbearing age.